Notice for additional service of cooperating the D-wall tester - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the notice for additional service of cooperating the D-wall tester of BRACU new campus development project.